Decontamination of Aspergillus parasiticus in rice by dielectric barrier discharge cold plasma: Variable effects and mechanism of degradation - Zhu Shuo; Yan Zhongjun; Shanshan Shi; Ai Zhi; Chenghong Wang; Fei Shen (Czech Journal of Food Sciences, 2025)
Rice is prone to be contaminated with spoilage or toxigenic fungi during harvest, storage and processing, with Aspergillus species being the most frequent. It is crucial to develop effective sterilisation technologies for mycotoxin prevention and food safety. In this study, sterilised rice infected by Aspergillus parasiticus strain was treated by dielectric barrier discharge (DBD) cold plasma. Various parameters, including moisture content, oxygen content, treatment time and voltage were tested. Furthermore, sterilisation mechanism of Aspergillus parasiticus by cold plasma was also explored. Results indicated that decontamination effect could be significantly affected by moisture content, oxygen concentration, voltage and treatment time. A 99.89% degradation rate against Aspergillus parasiticus was achieved at 90 kV after 5 min. Cold plasma could reduce the initial concentration of 6.05 to 2.28 CFU.mL-1 within 240 s, and to thoroughly decontamination within 360 s. In addition, cold plasma treatment destroyed the integrity of Aspergillus parasiticus cell membrane, resulting in a reduction in mycelium biomass and dry weight, as well as a significant decrease in intracellular Ca2+Mg2+-adenosine triphosphatase (ATPase) activity. These findings demonstrate the potential of cold plasma technology for environmentally friendly sterilisation of hazardous fungi in grain system.